2014
DOI: 10.1159/000362585
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on the Prevention, Screening, Early Diagnosis and Treatment of Colorectal Tumors in China: Chinese Society of Gastroenterology, October 14-15, 2011, Shanghai, China

Abstract: Background: Colorectal cancer (CRC) is steadily increasing in China. Colorectal adenoma (CRA) is the most important precancerous disease of CRC. Screening for colorectal tumors can aid early diagnosis. Advances in endoscopic mucosal resection and endoscopic submucosal dissection can aid the early treatment of colorectal tumors. Furthermore, because of high risk of recurrence after removal of adenomas under endoscopy, factors contributing to recurrence, the follow-up mode and the interval established, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 119 publications
1
27
1
2
Order By: Relevance
“…A scientific team from Oakland estimated that the increase in number with age was similar for both men and women, with prevalence rising across all 5‐year age categories, reaching a peak at 70‐74 years of age. A 2011 study reported that the highest incidence of colorectal tumors in the age range of 75‐80 years 22 . Our findings not only support the current Chinese consensus, but also suggest that colonoscopists should focus on elderly patients with multiple polyps who may be at risk of CRC.…”
Section: Discussionsupporting
confidence: 85%
“…A scientific team from Oakland estimated that the increase in number with age was similar for both men and women, with prevalence rising across all 5‐year age categories, reaching a peak at 70‐74 years of age. A 2011 study reported that the highest incidence of colorectal tumors in the age range of 75‐80 years 22 . Our findings not only support the current Chinese consensus, but also suggest that colonoscopists should focus on elderly patients with multiple polyps who may be at risk of CRC.…”
Section: Discussionsupporting
confidence: 85%
“…This consensus was developed on the basis of the ‘comprehensive prevention’ paragraph set forth in the Chinese consensus on screening, early diagnosis, early therapy, and prevention of colorectal cancer issued by the Chinese Society of Gastroenterology, CMA, in October 2011, as well as the progress in relevant international and domestic research achieved over the past 5 years. The Chinese Consensus on the Prevention of Colorectal Cancer (2016, Shanghai) conference was held on 8 May 2016 in Shanghai, hosted by the Chinese Society of Gastroenterology, CMA and its Committee on Gastrointestinal Tumors, and organized by the Division of Gastroenterology and Hepatology, Renji Hospital, School of Medicine, Shanghai Jiao Tong University and the Shanghai Institute of Digestive Disease.…”
Section: Levels Of Quality Of Evidence and Criteria Of Levels Of Recomentioning
confidence: 99%
“…Most of the clinical intervention studies on NSAIDs such as aspirin and COX‐2 inhibitors did not categorize whether it was for primary (prevention of initial development of adenoma) or secondary prevention (prevention of recurrence after adenoma resection) . However, clinical trials and epidemiological studies suggested that regular administration of aspirin could reduce the recurrence of adenoma and decrease the incidence and mortality of colorectal neoplasms …”
Section: Secondary Prevention Of Sporadic Cramentioning
confidence: 99%
“…Оценка тенденций заболеваемости и смертности позволила выявить снижение данных параметров в более развитых странах (США и Японии) за счет внедрения программ скрининга и раннего обнаружения КРР, реализуемых с 1990-х годов) [1]. В настоящее время скрининговые программы приняты и широко используются различными обществами [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionunclassified
“…Идея быстро привлекла внимание ученых по всему миру. На данный момент gFOBT является самым распространенным скрининговым тестом в мире, он широко используется в ряде европейских стран [3, 4], Канаде [5], США [6][7][8], Австралии, Китае и Японии [11]. В РФ тест использовался для диспансеризации населения до 2018 г.…”
Section: Introductionunclassified